Identification of Students’ Honesty Levels by Online Proctored Examinations in Higher Education Environment - Fitria Herliana; Susanna Susanna; Elisa Elisa; Ahmad Farhan (Postgraduate, University of Mataram, 2022)
This study aimed to identify the honesty level of students in online exams assisted by supervisory robots on the autoproctor application as an effort to improve the quality of online learning. The sample of this study were 34 students majoring in Physics Education FKIP USK who were selected randomly. Data were collected from test results using a google form embedded the autoproctor to detect student honesty during online exams and student response results from an honesty questionnaire based on four indicators developed by Ashton, M. C, et.al namely: sincerity, fairness, greed avoidance, and modesty. The data were analyzed using quantitative descriptive analysis. This study shows the honesty level of students recorded by the application is medium level and is supported by the results of honesty questionnaire responses. The response results show the level of honesty is in the very high to the medium range, while the test results using the autoproctor are in the very high to the very low range. There were some students who detected high honesty levels based on the results of the questionnaire responses but were detected very low on the autoproctor application. In applications, it was found evidence of fraud by students but they were not true after further observation, so it was necessary to inform the rules that must be obeyed using this application before the test. The findings of this study could be the basis for sustainable professional development using the autoproctor application in detecting student honesty in online exams